Economic Development Leads to Stronger Support among Religious Individuals for Clerical Influence in Politics - Lu, Yun (2022)
The secularization paradigm suggests that economic development should lead to the decline of clerical influence in politics. However, this suggestion is challenged by the fact that there is widespread support for clerics who try to transform politics according to religious precepts in many developed societies. In order to address this question, the present study examines how national economic development moderates the relationship between individual-level religiosity and attitudes towards clerical influence in politics, using the fourth and fifth waves of the World Values Survey data from 54 national samples. Multilevel regression models show that, first, religious individuals are more likely to support clerics’ political influence than nonreligious individuals. Moreover, the effects of individual religiosity in this regard depend on the economic context. In less developed societies, there is no significant difference between religious and nonreligious individuals regarding their attitudes toward clerical influence in politics. However, religious individuals become more supportive of clerical influence in politics in more developed countries.
Keywords: clerical influence in politics; world values survey; Economic Development; Secularization